IMPLEMENTASI KURIKULUM MERDEKA BELAJAR DALAM MENINGKATKAN MUTU PEMBELAJARAN PAI DI SMK NEGERI 1 KOTA BIMA - Kusniadin, Imam; Salam, Agus; Kaharuddin, Kaharuddin (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2025)
Many teachers still find it difficult to design learning materials that are in accordance with the new curriculum. It has been found that teachers' lack of understanding of the Merdeka Curriculum is one of the obstacles in its implementation. So the purpose of this study is to find out how the implementation of this curriculum can have an effective impact on the quality of PAI learning at SMK 1 Kota Bima. This research uses qualitative research. Data collection techniques are observation, documentation and interviews. Data analysis techniques are Data Reduction, Data Presentation and Conclusion Drawing. Based on the results of this study, it shows that there is a positive impact on the quality of learning. Teachers have more flexibility in developing learning materials and methods that are relevant to students' lives, while students become more active, creative, and motivated in learning.